2016
DOI: 10.1175/jhm-d-15-0121.1
|View full text |Cite
|
Sign up to set email alerts
|

The Evaporative Demand Drought Index. Part I: Linking Drought Evolution to Variations in Evaporative Demand

Abstract: Many operational drought indices focus primarily on precipitation and temperature when depicting hydroclimatic anomalies, and this perspective can be augmented by analyses and products that reflect the evaporative dynamics of drought. The linkage between atmospheric evaporative demand E0 and actual evapotranspiration (ET) is leveraged in a new drought index based solely on E0—the Evaporative Demand Drought Index (EDDI). EDDI measures the signal of drought through the response of E0 to surface drying anomalies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
207
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(210 citation statements)
references
References 32 publications
1
207
0
2
Order By: Relevance
“…Considering the importance of proactive disaster managements (Wilhite et al, ), monitoring early‐stage droughts is crucial to prepare for disastrous droughts that can follow. It has been shown that some drought events in the CONUS were led by earlier above‐normal ET p (Hobbins et al, ; McEvoy et al, ), thus emphasizing the importance of tracking the heat wave‐driven droughts. On the contrary to SEDI, a precipitation‐based drought index such as SPI and SPEI is unlikely able to detect the flash drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of proactive disaster managements (Wilhite et al, ), monitoring early‐stage droughts is crucial to prepare for disastrous droughts that can follow. It has been shown that some drought events in the CONUS were led by earlier above‐normal ET p (Hobbins et al, ; McEvoy et al, ), thus emphasizing the importance of tracking the heat wave‐driven droughts. On the contrary to SEDI, a precipitation‐based drought index such as SPI and SPEI is unlikely able to detect the flash drought.…”
Section: Discussionmentioning
confidence: 99%
“…In remote sensing of drought, ET has been a common indicator (AghaKouchak et al, ; Anderson et al, ; Mu et al, ; Otkin et al, ; Yao et al, ). Several indices solely depending on the potential and/or actual ETs were proposed and evaluated in drought characterization studies (e.g., Hobbins et al, ; Kim & Rhee, ; McEvoy et al, ; Vicente‐Serrano et al, ). The potential ET was combined with a precipitation‐based drought index (e.g., Beguería et al, ; Vicente‐Serrano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Partnerships among the High Plains Regional Climate Center, NDMC, NIDIS, and NCCSC have enabled the coproduction of quarterly drought and climate summaries for WRR and the surrounding area (Wind River Indian Reservation Drought and Climate Summary). The partnership with WWA is supporting the testing of innovative drought tools such as the EDDI for the WRR (Hobbins et al 2016), and providing an overall evaluation of the project. The summaries and EDDI together provide the infrastructure for monitoring and early warning systems, and support decision-making on the ground.…”
Section: Regional Climate Response Collaborativesmentioning
confidence: 99%
“…NOAA's ET r has been validated across western CONUS (Lewis et al, 2014) and the Texas High Plains (Moorhead et al, 2015), and while not yet deemed sufficiently accurate for the traditional use of ET r in field-scale irrigation scheduling, it nonetheless remains a highly leveraged product with uses across many other agricultural and water resource sectors. For example, it is used in irrigation support in agriculture away from agrometeorological stations; for water resource managers charged with estimating landscape-scale actual ET such as the U.S. Geological Survey's National Water Census for which it is under consideration (James Verdin, personal communication, 2015); as a climatology for the National Weather Service's (NWS) Forecast Reference ET product (NWS, 2015); and in multiple monitoring and prediction activities, including underpinning an agricultural drought index (the Evaporative Demand Drought Index, EDDI; Hobbins et al, 2016) and to support the U.S. Forest Service's seasonal forecasting of wildfire-suppression costs (Ham et al, 2014).…”
Section: Reference Evapotranspiration Reanalysismentioning
confidence: 99%